A solid electrolyte material and its preparation method and application
By using Li9MP4-xAsx as a solid electrolyte material, the problem of unstable interface between solid electrolyte and electrode in all-solid lithium batteries is solved, high ion and electron conductivity is achieved, and the cycle stability performance of the battery is improved.
Patent Information
- Application Number
- CN202311808431.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-12-26
AI Technical Summary
In the existing all-solid-state lithium battery technology, the interface contact between the solid electrolyte and the electrode is poor and the interface is unstable, resulting in insufficient ion transmission efficiency and cyclic stability performance.
Li9MP4-xAsx (0
It improves lithium ion conductivity and electronic conductivity, reduces interface impedance, enhances stability to lithium, solves the problem of interface instability between sulfur-based solid electrolytes and electrodes, and improves the cycle stability performance of all-solid-state batteries.
Smart Images

Figure CN117913349B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery application, and in particular relates to a solid electrolyte material and a preparation method and application thereof. Background Art
[0002] In the pursuit of energy storage systems with higher energy density, higher safety performance, and longer cycle life, all-solid-state batteries have become one of the most promising next-generation energy storage batteries because of their non-flammability, high temperature resistance, and ability to be directly used on the surface of Li metal negative electrodes. In order for all-solid-state batteries to operate efficiently and stably, the following conditions must be met: ① The ionic conductivity of the solid electrolyte material should be comparable to that of the electrolyte, at least 10 -4 S / cm; ② The electrode / electrolyte interface has good contact, low interface resistance, high electrochemical stability, and good interface kinetic performance. Although the concept of all-solid-state batteries has been proposed for more than 60 years, the shortcomings of ion transmission efficiency, cycle stability, production cost, etc. make their promotion and application in real life still quite challenging.
[0003] Currently, the solid electrolytes with the highest ionic conductivity come from the sulfur family represented by LGPS and LPSX, but the very active PS bonds are easily broken during the charge and discharge cycle to form impurities that damage the health of the battery. Such side reactions are particularly prone to occur at the electrolyte / electrode interface. The electroplating and stripping of lithium metal will cause the interface to have both ions and electrons, which can easily induce the breakage of PS bonds and generate impurities with low ionic conductivity and high electronic conductivity. The cracks and impurities produced by the decomposition reaction induce the uneven deposition of lithium to form lithium dendrites, which in turn bring electrons and lithium sources, further promoting the decomposition reaction of nearby electrolytes.
[0004] To solve the vicious cycle at the interface, it is necessary to consider the negative electrode / electrolyte interface and the positive electrode / electrolyte interface separately. The side reactions between the negative electrode and the solid electrolyte are usually caused by ions in the solid electrolyte that are easily reduced by lithium metal, such as oxygen and sulfur elements commonly found in solid electrolyte materials, which easily form thermodynamically very stable byproducts Li2O and Li2S with lithium. In the interface between the positive electrode and the solid electrolyte, the side reactions are often caused by the solid electrolyte and conductive carbon that have low lithium stability, etc. In order to accelerate the electron conduction in the positive electrode material, conductive carbon materials (such as acetylene black, Ketjen black, etc.) are usually mixed into it during the assembly of the all-solid-state battery; in order to accelerate the ion conduction rate between the positive electrode and the electrolyte, electrolyte materials are usually mixed into it to increase the contact area. The combination of conductive carbon and solid electrolyte (especially sulfur-based solid electrolyte) as a positive electrode material additive has been proven to have adverse effects: the presence of conductive carbon not only leads to large interfacial charge transfer resistance, but also aggravates the electrochemical decomposition of sulfur-based solid electrolytes in the composite positive electrode and at the positive electrode / solid electrolyte interface. How to ensure high-speed ion conduction while maintaining good cycle stability performance of all-solid-state batteries is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a solid electrolyte material and its preparation method and application in view of the above-mentioned deficiencies in the prior art. The preparation method of the solid electrolyte material is simple, and it has high ionic conductivity and electronic conductivity, low interfacial impedance and high stability to lithium. It can be used as a protective layer of sulfur-based solid electrolyte to prevent it from directly contacting lithium metal to reduce the occurrence of side reactions; it can be used as an interface material between lithium metal negative electrode and solid electrolyte to provide a good environment for electroplating / stripping of the negative electrode surface during charging and discharging; it can be used as a positive electrode additive to solve the problem that the conductive carbon in the current composite positive electrode material aggravates the electrochemical decomposition of sulfur-based solid electrolytes, resulting in a decrease in battery cycle performance.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The first object of the present invention is to provide a solid electrolyte material having the following chemical formula Li9MP 4-x As x , 0<x≤4, where M is any one of Al, Ga, and In elements, with M 3+ Form participation Li9MP 4-x As x formation.
[0008] Furthermore, the crystal of the solid electrolyte material is a cubic phase structure. P- 43 n Space group. P -43 nThe standard card number is no.218.
[0009] Furthermore, the lithium ion conductivity is not less than 1*10 -4 S / cm.
[0010] Furthermore, the M is Al.
[0011] Furthermore, at 70°C, the lithium ion diffusion coefficient in the solid electrolyte material is greater than 2.1×10 - 12 m 2 / s.
[0012] The second object of the present invention is to provide a method for preparing the above-mentioned solid electrolyte material, comprising the following specific steps:
[0013] Step S1, in an inert gas atmosphere, each element is mixed according to Li9MP 4-x As x The chemical stoichiometric ratio in the mixture is weighed, and ball milled to mix the mixture to obtain a ball milled material;
[0014] Step S2, under an inert gas atmosphere, dry-pressing and granulating the ball mill material to obtain an intermediate, sintering the intermediate in a closed tube to obtain a solid product, and crushing the obtained solid product to obtain a solid electrolyte material.
[0015] Furthermore, in step S2, the sintering process is to heat up to 500-700°C at a rate of 5°C / min under an argon atmosphere, keep the temperature at 500-700°C for 24-48 hours for solid phase synthesis reaction, and slowly cool down to room temperature at a rate of 0.5°C / min after the reaction is completed.
[0016] A third object of the present invention is to provide a solid electrolyte comprising the above-mentioned solid electrolyte material.
[0017] A fourth object of the present invention is to provide a solid electrolyte membrane comprising the above-mentioned solid electrolyte as a main component.
[0018] The fifth object of the present invention is to provide a lithium-ion battery, which is a lithium-ion battery having a positive electrode including a positive electrode active material layer, an electrolyte layer and a negative electrode including a negative electrode active material layer, and at least one of the positive electrode active material layer, the electrolyte layer and the negative electrode active material layer contains the above-mentioned solid electrolyte material.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention provides a solid electrolyte material having the following chemical formula: Li9MP 4-x As x, 0<x≤4, where M is any one of Al, Ga, and In elements, with M 3+ Form participation Li9MP 4-x As x By using Li9AlP4 as the matrix, As with a larger radius and smaller electronegativity 3- Replace P 3- , by broadening the lithium ion transmission channel to improve ionic conductivity; by increasing the lattice softness to reduce the activation energy barrier; by reducing the band gap to improve electronic conductivity.
[0021] (2) The present invention uses Li9MP 4-x As x (0<x≤4) isolates the direct contact between the solid electrolyte and the negative electrode, solving the problem of solid electrolyte reacting with lithium and causing battery failure in practical applications. It not only ensures efficient ion transmission, but also ensures good interface stability, which is conducive to solving the problems of poor solid-solid interface contact and interface instability between sulfide solid electrolyte and electrode in existing all-solid-state lithium battery technology.
[0022] (3) The present invention introduces a higher content of As to make Li9MP 4-x As x (0<x≤4) It has high ionic conductivity and high electronic conductivity at the same time. In the composite positive electrode material of all-solid-state batteries, it can replace the traditional combination of solid electrolyte and conductive carbon, and provide a solution to the side reaction decomposition of sulfur-based solid electrolyte when it contacts activated carbon, which leads to reduced cycle stability and reduced rate performance.
[0023] (4) The process of the present invention is simple and efficient, the preparation process is simple, and it is suitable for commercial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The scanning electron microscope images of the base material Li9AlP4 and Examples 1, 2, and 3;
[0025] Figure 2 This is the mapping map of the matrix material Li9AlP4;
[0026] Figure 3 is a Rietveld analysis result diagram of the powder X-ray diffraction pattern of Example 3 annealed at 700° C.;
[0027] Figure 4 is the X-ray diffraction pattern of Examples 1, 2, 3, and 4;
[0028] Figure 5 The solid electrolyte material Li9MP of the present invention 4-x As xThe ionic conductivity of the matrix at room temperature and at 70°C 7 Li PFG NMR diffusion coefficient measurement results;
[0029] Figure 6 For Comparative Example 1 (solid electrolyte Li not compounded with the example 10 SnP2S 12 ) assembled lithium metal symmetric battery, at room temperature at 0.05 mA / cm 2 The charging and discharging diagram below;
[0030] Figure 7 In order to assemble a symmetrical battery by combining Example 3 and Comparative Example 1, the 2 Schematic diagram of charge and discharge under Figure 6 ). DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0032] Example 1
[0033] The invention provides a method for preparing a solid electrolyte material Li9AlP2As2.
[0034] The specific steps are as follows:
[0035] Step S1, under an inert gas atmosphere, weigh according to the stoichiometric ratio of Li: Al: P: As = 9: 1: 2: 2, put the powder into a ball mill at a ball-to-material ratio of 40:1, and ball mill at a speed of 360 r / min for 36 hours to obtain a ball mill material;
[0036] Step S2, in an inert gas atmosphere, placing the ball abrasive into a mold and dry pressing it under a pressure of 3t into a sheet material with a thickness of about 1mm, granulating it after demolding, and encapsulating it in a vacuum quartz tube;
[0037] Step S3, place the quartz tube in a tubular furnace, heat it to 500~700℃ at a rate of 5℃ / min, keep it at 500~700℃ for 24~48h to carry out solid phase synthesis reaction, and after the reaction, slowly cool it to room temperature at a rate of 0.5℃ / min, grind the obtained solid product to obtain the all-solid-state battery additive Li9AlP2As2 that can be composited with the solid electrolyte to improve the overall performance. Steps S1-S3 are all performed in a glove box protected by inert gas. It should be noted here that the material can be guaranteed to be within the annealing temperature range of 500~700℃ and the insulation time range of 24~48h. P -43 n The annealing temperature and holding time only affect the crystallinity. The appropriate temperature can be selected within this range according to the requirements for material stability and lithium interface impedance.
[0038] Example 2
[0039] The present invention provides a method for preparing a solid electrolyte material Li9AlPAs3.
[0040] The specific steps are as follows:
[0041] Step S1, under an inert gas atmosphere, weigh according to the stoichiometric ratio of Li: Al: P: As = 9: 1: 2: 3, put the powder into a ball mill at a ball-to-material ratio of 40:1, and ball mill at a speed of 360 r / min for 36 hours to obtain a ball mill material;
[0042] Step S2, in an inert gas atmosphere, placing the ball abrasive into a mold and dry pressing it under a pressure of 3t into a sheet material with a thickness of about 1mm, granulating it after demolding, and encapsulating it in a vacuum quartz tube;
[0043] Step S3, place the quartz tube in a tubular furnace, heat it to 500~700℃ at a rate of 5℃ / min, keep it at 500~700℃ for 24~48h to carry out solid phase synthesis reaction, and after the reaction, slowly cool it to room temperature at a rate of 0.5℃ / min, grind the obtained solid product to obtain the all-solid-state battery additive Li9AlP2As3 that can be composited with the solid electrolyte to improve the overall performance. Steps S1-S3 are all performed in a glove box protected by inert gas. It should be noted here that the material can be guaranteed to be within the annealing temperature range of 500~700℃ and the insulation time range of 24~48h. P -43 n The annealing temperature and holding time only affect the crystallinity. The appropriate temperature can be selected within this range according to the requirements for material stability and lithium interface impedance.
[0044] Example 3
[0045] The present invention provides a method for preparing a solid electrolyte material Li9AlPAs4.
[0046] The specific steps are as follows:
[0047] Step S1, under an inert gas atmosphere, weigh according to the stoichiometric ratio of Li: Al: P: As = 9: 1: 2: 4, put the powder into a ball mill at a ball-to-material ratio of 40:1, and ball mill at a speed of 360 r / min for 36 hours to obtain a ball mill material;
[0048] Step S2, in an inert gas atmosphere, placing the ball abrasive into a mold and dry pressing it under a pressure of 3t into a sheet material with a thickness of about 1mm, granulating it after demolding, and encapsulating it in a vacuum quartz tube;
[0049] Step S3, place the quartz tube in a tube furnace, heat it to 500~700℃ at a rate of 5℃ / min, keep it at 500~700℃ for 24~48h to carry out solid phase synthesis reaction, and after the reaction, slowly cool it to room temperature at a rate of 0.5℃ / min, grind the obtained solid product to obtain the all-solid-state battery additive Li9AlP2As4 that can be composited with the solid electrolyte to improve the overall performance. Steps S1-S3 are all performed in a glove box protected by inert gas. It should be noted here that the material can be guaranteed to be within the annealing temperature range of 500~700℃ and the insulation time range of 24~48h. P -43 n The annealing temperature and holding time only affect the crystallinity. The appropriate temperature can be selected within this range according to the requirements for material stability and lithium interface impedance.
[0050] Example 4
[0051] The invention provides a method for preparing a solid electrolyte material Li9GaAs4.
[0052] The specific steps are as follows:
[0053] Step S1, under an inert gas atmosphere, weigh according to the stoichiometric ratio of Li:Ga:As=9:1:4, put the powder into a ball mill at a ball-to-material ratio of 40:1, and ball mill for 36 hours at a speed of 360 r / min to obtain a ball mill material;
[0054] Step S2, in an inert gas atmosphere, placing the ball abrasive into a mold and dry pressing it under a pressure of 3t into a sheet material with a thickness of about 1mm, granulating it after demolding, and encapsulating it in a vacuum quartz tube;
[0055] Step S3, place the quartz tube in a tubular furnace, heat it to 500~700℃ at a rate of 5℃ / min, keep it at 500~700℃ for 24~48h to carry out solid phase synthesis reaction, and after the reaction, slowly cool it to room temperature at a rate of 0.5℃ / min, grind the obtained solid product to obtain the all-solid-state battery additive Li9AlP2As2 that can be composited with the solid electrolyte to improve the overall performance. Steps S1-S3 are all performed in a glove box protected by inert gas. It should be noted here that the material can be guaranteed to be within the annealing temperature range of 500~700℃ and the insulation time range of 24~48h. P -43 n The annealing temperature and holding time only affect the crystallinity. The appropriate temperature can be selected within this range according to the requirements for material stability and lithium interface impedance.
[0056] refer to Figure 1 , the solid electrolyte material prepared in Example 1-3 was loaded into a tablet press, kept at 3 MPa for 1 min, the obtained sheet material was broken, and its cross section was scanned after 2 hours. Under a small pressure, the material was transformed into a block and did not loosen within 2 hours, showing good adhesion. In addition, bright stripes can be seen on the Li9AlP4 scan, which is caused by the charging effect caused by poor conductivity. As doping proceeds, the electronic conductivity of the material increases and the stripes disappear.
[0057] refer to Figure 2 , which is the mapping spectrum of the matrix material Li9AlP4. In the scanning results, the atomic percentages of Al and P are 20.08% and 79.92%, respectively, which conforms to the relationship of 1:4.
[0058] refer to Figure 3 , which is the XRD comparison diagram of the solid electrolyte material prepared in Examples 1-4. It can be seen from the figure that as the doping progresses, the XRD diffraction peaks collectively shift to small angles relative to the matrix material, proving that the unit cell parameters gradually increase. In addition to the diffraction peaks of the target phase, there are no other obvious impurity peaks in the spectrum.
[0059] refer to Figure 4 , the Rietveld analysis result of the powder X-ray diffraction pattern of Example 3 annealed at 700°C. In the figure, the black dots represent the observed intensity, the black line represents the calculated intensity, the line below represents the difference between the two, and the Bragg position is marked with a dotted line; when the annealing temperature is reduced, the crystallinity will decrease accordingly, the Li interface impedance will decrease, but the stability will also decrease slightly. The performance on the XRD spectrum is: the diffraction angle corresponding to the characteristic peak does not change, but the relative intensity of the peaks changes. The higher the crystallinity, 2 θThe greater the relative intensity ratio of the diffraction peaks at 25° and 41.6°, the greater the relative intensity ratio of the diffraction peaks at 25° and 41.6°. For the target compound, when the application requirements in all-solid-state batteries are different, the requirements for crystallinity are also different. When the diffraction angle of the peak does not change, it is reasonable for the diffraction peak intensity ratio to fluctuate up and down.
[0060] refer to Figure 5 , is the solid electrolyte material Li9MP of the present invention 4-x As x The ionic conductivity of the matrix at room temperature and at 70°C 7 Li PFG NMR diffusion coefficient measurement results. It can be found from the figure that with the increase of x, the macroscopic ion conductivity and the microscopic ion diffusion rate are positively correlated, indicating that As doping has a positive effect on the improvement of ion transport performance.
[0061] Comparative Example 1
[0062] Comparative Example 1 is a type of sulfide solid electrolyte material Li with low stability to lithium metal 10 SnP2S 12 The preparation method thereof is:
[0063] Step S1, weigh P2S5, Li2S and SnS2 according to the ratio of Li2S: SnS2: P2S5 = 5:1:1 (molar ratio), put the powder into a ball mill at a ball-to-material ratio of 40:1, and ball mill at a speed of 550 r / min for 8 h to obtain a ball mill material;
[0064] Step S2, in an inert gas atmosphere, placing the ball abrasive into a mold and dry pressing it under a pressure of 3t into a sheet material with a thickness of about 1mm, granulating it after demolding, and encapsulating it in a vacuum quartz tube;
[0065] Step S3, placing the quartz tube in a tube furnace, heating it to 550°C at a rate of 0.5°C / min, and keeping it warm for 48 hours in an argon atmosphere for solid phase synthesis reaction. After the reaction is completed, slowly cooling it to room temperature at a rate of 1°C / min, and crushing the obtained solid product to obtain a sulfide solid electrolyte material Li 10 SnP2S 12 Steps S1-S3 are all performed in a glove box protected by inert gas.
[0066] The solid electrolyte materials prepared in Examples 1-4 and Comparative Example 1 were tested for performance:
[0067] (1) Conductivity test
[0068] In a glove box, by using a powder forming mold made of stainless steel and with an insulating layer on the top and bottom, Examples 1, 2, 3, 4 and the base material Li9AlP4 were pressed into sheets with a diameter of 10 mm under a pressure of 360 MPa. The electrochemical workstation was used to perform AC impedance tests at different temperatures to obtain ionic conductivity, and the activation energy was calculated based on the relationship between conductivity and temperature; the electrochemical workstation was used to perform polarization tests to obtain electronic conductivity.
[0069] Test results:
[0070] Compared with the matrix Li9AlP4, the ionic conductivity and electronic conductivity of Examples 1, 2, and 3 after As substitution are significantly improved, and the magnitude is positively correlated with the arsenic content; the activation energy is significantly reduced, and the value is negatively correlated with the arsenic content. For Example 4 (Li9GaAs4) in which the M element is replaced, the conductivity is improved more significantly. The specific results are shown in Table 1:
[0071] Table 1.
[0072]
[0073] (2) Lithium metal stability test
[0074] Symmetrical cells were prepared using Comparative Example 1 and labeled as Li / Li 10 SnP2S 12 / Li; a symmetrical battery was prepared by combining Example 3 with Comparative Example 1, marked as Li / Li9AlAs4-Li 10 SnP2S 12 - Li9AlAs4 / Li; at room temperature, 0.05~0.1 mA / cm 2 Long-term cycle stability test was carried out at different current densities.
[0075] Test results:
[0076] Symmetrical battery Li / Li 10 SnP2S 12 / Li at room temperature 0.05 mA / cm 2 The charge and discharge cycle diagram is as follows Figure 6 As shown in the figure, after 45 hours of cycling, the interfacial voltage increases rapidly, indicating that Li 10 SnP2S 12 Severe decomposition, resulting in battery failure. Symmetrical battery Li / Li9AlAs4-Li 10 SnP2S 12 -Li9AlAs4 / Li at room temperature 0.05~0.1 mA / cm 2 The charge and discharge cycle diagram is as follows Figure 7As shown, the battery is at 0.05 mA / cm 2 After cycling for 1000 hours at a current density of 0.1 mA / cm 2 The cycle continued for more than 2000 hours at the current density, showing good cycle stability. This experiment shows that Li9AlAs4 has good protection for solid electrolytes and good electrochemical stability for metallic lithium, which is beneficial to improving the cycle stability of all-solid-state batteries.
[0077] For matters not mentioned above, the prior art applies.
[0078] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A solid electrolyte material, characterized in that: The solid electrolyte material has the following chemical formula Li9MP 4- x As x , 0<x≤4, where M is any one of Al, Ga, and In elements, with M 3+ Form participation Li9MP 4-x As x The solid electrolyte material is formed by a crystal structure of a cubic phase. P-43n Space group.
2. The solid electrolyte material according to claim 1, characterized in that At room temperature, the lithium ion conductivity is not less than 0.96×10 -3 ~6.08×10 -3 S / cm.
3. The solid electrolyte material according to claim 1, characterized in that At room temperature, the electronic conductivity is not less than 10 -7 S / cm.
4. The solid electrolyte material according to claim 1, characterized in that The M is Al.
5. The solid electrolyte material according to claim 4, characterized in that At 70°C, the lithium ion diffusion coefficient of the solid electrolyte material is greater than 2.1×10 -12 m 2 / s.
6. A method for preparing a solid electrolyte material according to any one of claims 1 to 5, characterized in that: The specific steps include: S1. In an inert gas atmosphere, each element is mixed according to Li9MP 4-x As x The chemical stoichiometric ratio in the mixture is weighed, and ball milled to mix the mixture to obtain a ball milled material; S2. In an inert gas atmosphere, the ball mill is dry-pressed and granulated to obtain an intermediate, the intermediate is sintered in a closed tube to obtain a solid product, and the obtained solid product is crushed to obtain a solid electrolyte material.
7. The preparation method according to claim 6, characterized in that: In step S2, the sintering process is to heat up to 500-700°C at a rate of 5°C / min under an argon atmosphere, keep the temperature at 500-700°C for 24-48 hours for solid phase synthesis reaction, and slowly cool down to room temperature at a rate of 0.5°C / min after the reaction is completed.
8. A solid electrolyte, characterized in that The method comprises the solid electrolyte material according to any one of claims 1 to 5.
9. A solid electrolyte membrane, characterized in that: Contains the solid electrolyte according to claim 8 as a main component.
10. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, characterized in that: At least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer includes the solid electrolyte material according to any one of claims 1 to 5.
Citation Information
Patent Citations
Modified argyrodite compound solid electrolyte as well as preparation method and application thereof
CN114789993A
Solid electrolyte and a method for preparing the same
KR1020030094758A